Importance of screening for unexpected antibodies in compatibility testing - Zúñiga Camacho, Pedro María; Cortés Buelvas, Armando Daniel; Rosado de Cabas, Rosalba; García Gutiérrez, Marcela (Colombia Medica, 1992)
Four years of experience in pretransfusion tesis at the National Blood Bank, Colombian Red Cross, Santafé de Bogotá, Colombia, from 1987 to 1990, were assessed. Among 1,470 pretransfusion tests, 90 were found incompatibilities, and 30 (32.6%) had positive antibodies screen compatible cross matches. These results indicate the importance of antibody screen tests in patients to ensure a safe transfusion procedure.